ANALISIS KONTRASTIF PREFIKS ter- BAHASA KARO DAN BAHASA INDONESIA (Suatu Sumbangan untuk Pembelajaran Bahasa) - SANGGUP BARUS (BAHAS, 2014)
Contrastive analysis of prefix ter- in Karo language and Indonesian language is aimed to get understanding about the definition of contrastive analysis of prefix and the description about the difference of prefix ter- in Karo language and Indonesian language in case of form, distribution, function, and notion (a contribution to language instructional). Seen from the analysis, it can be found that contrastive analysis of prefix meant the research to compare form, distribution, function, and notion of the prefix of two languages or more by identifying the difference. Also, it was found the difference of the prefix ter- in Karo language and Indonesian language in distribution, function, and notion. Key words : Contrastive analysis, prefix ter-